Perbandingan Produksi, Kadar Lemak, dan Kadar Protein Susu Kambing Peranakan Ettawa yang Diberi Ampas Tahu - Anjuka, Nur Laila; Hendri, John; Sari, Rica Mega (Program Studi peternakan, 2023)
This research aims to determine whether there are differences in the production, fat content, and protein content of milk from Ettawa crossbreed goats given forage and forage plus tofu waste. To determine the measured parameters, statistical analysis was carried out using a two-sample t-test. The parameters measured in this study were the amount of milk production (ml/cow/day), fat content (%), and protein content (%). The results of the research showed that the average production, fat content, and protein content of milk from Ettawa crossbreed goats fed forage with added tofu waste and without tofu waste were respectively 765.83 ml/head/day and 343.33 ml/head/day; 5.71 % and 6.95 %; 3.89 % and 3.52 %. From the research results, it can be concluded that there is a difference between the amount of production, fat content, and protein content of Ettawa crossbreed goat milk given tofu waste.